10 Bowen St. - Leitch, Fran (Auckland University of Technology, 2008)
This project is a site specific based exploration into the boundaries between the domestic home and the navigation of the anxious corporeal body which dwells in the space. These connections open up ways of mapping anxiety brought on through intrusive thoughts surrounding contamination (in relation to Obsessive Compulsive Disorder). The corporal navigation of the domestic is fuelled by the thoughts and their control over the notions of fear and anxiety surrounding the transferring of contaminated material from the external temporal world (dust and organic matter) into the internal sterile environment through movement or fissures in the fabric of the dwelling. The project explores the notions of the domestic space being formed into a container for the intrusive thoughts through physical acts of decontaminating, containment, sealing and expelling the elements of dirt; the body and the home become a hybrid entity alluding to the extreme control which forms and takes over the domestic space.
Keywords: Containment; Decontamination; Domestic; Spatial; Control; Leakage